Insights into the process of creating a coach development programme: the opportunities and challenges of ethnodrama - Cassidy, T.; Kidman, L.; Dudfield, O. (Qualitative Research in Sport, Exercise and Health, 2015)
The purpose of the article is twofold. First is to provide insights into the practices of one Coach Director of a National Sport Organisation (NSO) as he endeavoured, over a two-year period, to create a coach development programme that was consistent with the principles of New Zealand`s Coach Development Framework (CDF). Second is to share our reflections on the experiences of reading ethnodrama scripts at a sport leadership conference, as we aimed to disseminate research in a way that was accessible and applicable to members of a professional community. This article stems from an on-going ethnographic research project that utilises a range of methods to describe, interpret and critique the `initiation`, `use` and `assessment` of the New Zealand CDF. The data sources used in the study were consistent with ethnographic fieldwork and included field notes, documentation from the NSO and the government agency dedicated to fostering a sport and recreation environment and interviews. Two semi-structured interviews were conducted with the NSO Coaching Director, each lasting between 120 and 180 min. The ethnodrama scripts described in this paper illustrate the progress the Coach Director made towards creating a coach development programme that was consistent with New Zealand`s CDF. Our reflections shed light on the challenges of using ethnodrama, albeit in an abridged form, as a vehicle for professional development, social change and cultural awareness.